Effect of atorvastatin on the most important mechanisms of arrhythmogenesis in patients with ST-elevated myocardial infarction - V. E. Oleynikov; M. V. Lukianova; E. V. Dushina; Yu. A. Barmenkova (Российский кардиологический журнал, 2019)
Aim. To study the effect of the 48-week atorvastatin therapy on the mechanisms of arrhythmogenesis, determined during daily ECG monitoring, in patients with ST-elevated myocardial infarction (STEMI).Material and methods. The study included 104 people. Patients were randomized into two groups: a high-dose statin therapy group who took 80 mg of atorvastatin per day, and a comparison group who received atorvastatin 20 mg/day for 48 weeks. Upon admission and every 12 weeks, the total cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol and triglycerides were determined. At the 7-9th day, 24th and 48th weeks of STEMI the daily ECG monitoring on 12 leads using the Holter Analysis-Astrocard complex (Meditek CJSC, Russia) with an assessment of the circadian dynamics of the heart rate, late ventricular potentials, duration, variability and dispersion of the QT interval, temporal and spectral parameters of heart rate variability, heart rate turbulence and the frequency of ventricular arrhythmias. Various cardiovascular events in the postinfarction period were taken as the end points.Results. Depending on the achievement/non-achievement of the LDL-С target level in the treatment process, two groups were identified: highly effective lipidlowering therapy “HET” — 51 people and relatively effective lipid-lowering therapy “RET” — 49 patients. In the HET group, QT dispersion regression was obtained from the 24th week of treatment; in the RET group, the dynamics of QTe disp, sdQTe, sdQTa values was not found. A positive transformation of all parameters characterizing the post-depolarization activity was revealed only in the HET group: a decrease in QRSf and HFLA, an RMS increase. Significant differences were obtained in the most of the parameters of both temporal and spectral analysis of HRV in the HET group. Clinically significant rhythm and conduction disturbances were more frequently recorded in patients of the RET group.Conclusion. Achieving the target LDL values in atorvastatin therapy in patients with STEMI is associated with the electrophysiological stability of the myocardium and the clinical well-being of patients in the post-infarction period.